Machlup on the Basing-Point System - Clark, J. M. (Quarterly Journal of Economics, 1949)
Journal Article Machlup on the Basing-Point System Get access J. M. Clark J. M. Clark Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 63, Issue 3, August 1949, Pages 315–321, https://doi.org/10.2307/1882257 Published: 01 August 1949